Cross-section of subsea umbilical and stress prediction of its structural components; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Solovev V. V. Vasilii Vasilevich (2017, 2017)
Title screen